1985
DOI: 10.1002/mar.4220020207
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses and advertising effects: Is the cup half full or half empty?

Abstract: A debate has arisen in this journal regarding the utility of psychophysiological measures in general; and of electroencephalographic measures in particular, for evaluating the specific effects of advertising executions. We briefly summarize the positions and replies that have been set forth. Although each is found to have something to contribute, it is also clear that additional basic research using complex persuasion materials in consumer settings is necessary before specific cognitive, emotional, and behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In particular, the self-assessment measures commonly used in marketing research rely totally on the ability and willingness of the respondent to accurately report their attitudes and/or prior behaviours (Petty and Cacioppo, 1983). Physiological responses, however, can be collected when respondents are directly participating in the behaviour, are difficult for subjects to control (although not difficult to affect), and although there are individual differences in physiological responding, variations in social situations and stimuli have also been shown to have a powerful effect across individuals (Cacioppo and Petty, 1985). As seen above though, neuromarketing has not been without critics and, even within academic circles, concerns have been raised over the ability of neurological methods to adequately take into account the panoply of relevant variables in marketing theories (e.g.…”
Section: Exploring and Delineating The Scope Of Neuromarketingmentioning
confidence: 98%
“…In particular, the self-assessment measures commonly used in marketing research rely totally on the ability and willingness of the respondent to accurately report their attitudes and/or prior behaviours (Petty and Cacioppo, 1983). Physiological responses, however, can be collected when respondents are directly participating in the behaviour, are difficult for subjects to control (although not difficult to affect), and although there are individual differences in physiological responding, variations in social situations and stimuli have also been shown to have a powerful effect across individuals (Cacioppo and Petty, 1985). As seen above though, neuromarketing has not been without critics and, even within academic circles, concerns have been raised over the ability of neurological methods to adequately take into account the panoply of relevant variables in marketing theories (e.g.…”
Section: Exploring and Delineating The Scope Of Neuromarketingmentioning
confidence: 98%
“…Because the tenuous validity of self-report data, specifically in terms of an individual's capacity to honestly report emotional responses (Cacioppo, Tassinary, & Berntson, 2000;Geiger & Newhagen, 1993;Gutek, 1978;Kipnis, 1997;Stayman & Aaker, 1993), the model also incorporates psychophysiological measures. Psychophysiological data can offer insight into the subconscious emotional responses individuals may have toward brands (Cacioppo & Petty, 1985;Wang & Minor, 2008). Physiological responses are involuntary and subconscious.…”
Section: Measures Prescribed By the Motivational Model Of Emotionmentioning
confidence: 99%
“…Indeed, the cognitive areas of organizational research, such as economic decision making 10,11 and information processing 12,13 have shown the greatest aptitude for incorporating modern brain imaging methodologies. In contrast, neuroimaging and other psychophysiological techniques have yet to make significant inroads into the more social psychologically oriented organizational disciplines—although constructs such as arousal have been of some interest in marketing research, for example 14 …”
Section: Organizational Cognitive Neurosciencementioning
confidence: 99%
“…EEG has so far probably been the most commonly used of all the direct cortical measuring methodologies within an organizational context. In particular, advertising research has made infrequent use of EEG for nearly 30 years 14,51–53 . Work on economic decisions has also used EEG 54 .…”
Section: What Can Brain Activity Tell Us About Organizational Researcmentioning
confidence: 99%